Las nuevas tecnologías de la información y la comunicación (n´tics) para el aprendizaje de la economía en los estudiantes de la Universidad Técnica de Cotopaxi , de la carrera de ingeniería comercial en el periodo 2015 - Chávez Chávez, Janeth Alexandra (2015)
The present thesis was elaborated at seeing the need to use of the New Technologies of the Information and the Communication (NTICS) in the students of the Technical University of Cotopaxi in the career of Commercial Engineering, in this case to study of the topic of economy, the same what at being a science that finds involved directly in the field in where the professional future will exert, does necessary that for his learning have new technological tools that allow to the students develop his competitions, skills and knowledges with the aim to be chords to the requirements of the current professional market. To fulfil with this work used the deductive method like method of investigation, the survey and interview like techniques of investigation, allowing know and confirm that it is necessary the application of these technological tools that combine the theoretical knowledges with the practice like is the creation of a manual for the preparation of staff in Microsoft Excel to study topics of economy, given that this program facilitates a lot of operations and has incorporated financial functions mathematics that adjust to the study of this topic. In the developing this manual will contribute to improve educational process of the university.